1994
DOI: 10.1177/039139889401701006
|View full text |Cite
|
Sign up to set email alerts
|

Blood compatibility of two different types of membrane oxygenator during cardiopulmonary bypass in infants

Abstract: The contact of blood with the artificial extracorporeal circuit causes a systemic inflammatory response due to blood activation. In this study, we compared two different paediatric membrane oxygenators used for extracorporeal circulation: a hollow fibre membrane oxygenator (Dideco Masterflo D-701, n = 10), and a flat sheet silicone membrane oxygenator (Avecor Kolobow 800-2A, n = 10). Blood compatibility was indicated by measuring complement activation as well as leukocyte and platelet activation. In patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…This was indicated by a similar increase of C3a in the hollow fiber and flat sheet groups during CPB whereas a difference was seen in the increase of elastase between the 2 groups. This is in contrast to results from a previous study in infants that indicated C3a was significantly higher in the flat sheet oxygenator group than in the hollow fiber oxygenator group (16). The difference between infants and adults may suggest that in infants complement activation as well as the subsequent leukocyte activation are more dependent on surface contact.…”
Section: Discussioncontrasting
confidence: 99%
“…This was indicated by a similar increase of C3a in the hollow fiber and flat sheet groups during CPB whereas a difference was seen in the increase of elastase between the 2 groups. This is in contrast to results from a previous study in infants that indicated C3a was significantly higher in the flat sheet oxygenator group than in the hollow fiber oxygenator group (16). The difference between infants and adults may suggest that in infants complement activation as well as the subsequent leukocyte activation are more dependent on surface contact.…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, there was a very large blood-membrane contact surface area in this system. Therefore, we expected to observe a considerable inflammatory response after CPB with this setup (Gu et al, 1994). We did not detect a TNF-α acute phase response and we found a late rise in IL-6 levels, with a comparable pattern in both the sham and the CPB group.…”
Section: Discussionmentioning
confidence: 61%
“…15,16 The hollow-fibre polypropylene membrane oxygenator with the smallest surface area resulted in significantly less C3a generation than the other types. 8 Although the oxygenators differ in configuration, the surface is the primary trigger for complement activation, and therefore the results are likely to be explained by the smaller contact surface area of the hollow-fibre membrane. 5,8 The difference that was observed between the silicone membrane (group 3) and the polypropylene membrane with approximately the same surface area (group 2), most likely represents the larger trigger of complement activation by the silicone than that of the polypropylene surface.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although the oxygenators differ in configuration, the surface is the primary trigger for complement activation, and therefore the results are likely to be explained by the smaller contact surface area of the hollow-fibre membrane. 5,8 The difference that was observed between the silicone membrane (group 3) and the polypropylene membrane with approximately the same surface area (group 2), most likely represents the larger trigger of complement activation by the silicone than that of the polypropylene surface. 3,9 It is well known that after the administration of protamine sulphate, the complement system is activated by the classical pathway.…”
Section: Discussionmentioning
confidence: 99%